Genome-wide identification and characterisation of Toll-like receptors in Chinese spiny frog (Quasipaa spinosa) - Li, Zehong; Gao, Zihan; Mo, Dexin; Zhu, Zifeng; Zhang, Jingqi; Liu, Mujin; Xiao, Han; Zhou, Meng; Gao, Teng; Liang, Rishen (Frontiers in Genetics, 2025)
IntroductionToll-like receptors (TLRs) are pattern recognition receptors essential for immune defense against pathogens, activating the host’s immune response by recognizing conserved pathogen structures. The Chinese spiny frog (Quasipaa spinosa), an amphibian native to southern China and northern Vietnam, has been severely impacted by recent infectious disease outbreaks caused by bacterial, viral, and parasitic infections, which threaten the sustainable development of the Q. spinosa farming industry. However, the roles of Q. spinosaTLRs (QsTLRs) in combating these exogenous pathogens have not yet been explored.MethodsIn the study, using the whole genome data of Q. spinosa, bioinformatics tools were employed to identify and analyze the TLR gene family. The bacteria Elizabethkingia miricola, a common pathogen, which causes the cataract disease and can lead to serious death of the frog. Here, we selected the bacteria to conduct the challenge experiment in order to characterize the immune responses of the TLR genes of Q. spinosa against bacterial infection.ResultsThe analysis identified 17 members of the TLR gene family in Q. spinosa. Phylogenetic analysis revealed that QsTLRs can be classified into seven subfamilies: TLR1, TLR3, TLR4, TLR5, TLR7, TLR11, and TLR13. Conserved synteny analysis indicated that Q. spinosa is more closely related to Rana temporaria than to Xenopus laevis. Protein structure prediction and motif analysis demonstrated that all QsTLRs are relatively conserved in both structure and function. mRNA expression levels of QsTLRs in spleen tissues were measured following stimulation with Elizabethkingia miricola, which revealing that 15 QsTLR genes exhibited up-regulation at various time points post-stimulation.DiscussionThese findings provide a comprehensive understanding of the QsTLR gene family and lay the groundwork for future studies exploring the functional evolution of the amphibian TLR gene family.